Bare Iron Oxide Nanoparticles as Drug Delivery Carrier for the Short Cationic Peptide Lasioglossin - Chiara Turrina; Sonja Berensmeier; Sebastian P. Schwaminger (MDPI AG, 2021)
New drug delivery systems are a potential solution for administering drugs to reduce common side effects of traditional methods, such as in cancer therapy. Iron oxide nanoparticles (IONs) can increase the drugs' biological activity through high binding efficiency and magnetically targeted drug delivery. Understanding the adsorption and release process of a drug to the carrier material plays a significant role in research to generate an applicable and controlled drug delivery system. This contribution focuses on the binding patterns of the peptide lasioglossin III from bee venom on bare IONs. Lasioglossin has a high antimicrobial behavior and due to its cationic properties, it has high binding potential. Considering the influence of pH, the buffer type, the particle concentration, and time, the highest drug loading of 22.7% is achieved in phosphate-buffered saline. Analysis of the desorption conditions revealed temperature and salt concentration sensitivity. The nanoparticles and peptide-ION complexes are analyzed with dynamic light scattering, zeta potential, and infrared spectroscopy. Additionally, cytotoxicity experiments performed on Escherichia coli show higher antimicrobial activity of bound lasioglossin than of the free peptide. Therefore, bare IONs are an interesting platform material for the development of drug-delivery carriers for cationic peptides.